Analisis Kepuasan Pengguna Terhadap Website Kharisma Classroom Menggunakan Metode PIECES - Sentosa, Chintia; Sudirman; Afifah (KHARISMA Tech, 2024)
The Kharisma Classroom is a website that supports students learning by allowing students to access materials anywhere and anytime using the internet. The use of the Kharisma Classroom website as a learning tool made researchers want to know the users level of satisfaction. To determine the level of user satisfaction on the Kharisma Classroom website, an analysis using the PIECES (Performance, Information, Economy, Control, Efficiency, Service) method was needed. Based on the variables from the PIECES method, the level of user satisfaction based on each variable was: Performance gets a score of 3.62, Information gets a score of 3.48, Economy gets a score of 3.83, Control gets a score of 3.6, Efficiency gets a score of 3.2, and Service obtained a value of 3.68. Based on the results of calculating the average satisfaction level for each variable in the PIECES method, it can be concluded that the average user was satisfied but still needs to make improvements in the future so that the Kharisma Classroom website service can be better.